Dialogue journals and traditional writing assignments: A comparison of writing in L2 German classrooms - Henry, Nick; Mandel, Hannes; VanderHeijden, Vincent (Foreign language annals, 2024)
Dialogue journals (DJs) are a type of extensive writing assignment, in which students write for the purpose of communication with their instructor. Previous research has shown that DJs can help students develop writing skills; however, few studies have analyzed how DJs compare with traditional prompt‐based assignments (TAs). The present study, therefore, presents a quasi‐experimental comparison of texts from first‐ and second‐year German classrooms that used either DJs or TAs. Analysis focused on five metrics: (1) word count, (2) sentence count, (3) words per sentence, (4) text‐type ratio (TTR), and (5) measure of textual lexical diversity (MTLD). Results for word and sentence count indicated that TA texts were longer. However, DJs resulted in more complex writing, as measured by sentence length, MTLD, and TTR. Taken together, results suggest that journals can promote writing that is both communicatively oriented and linguistically complex. The article concludes by offering suggestions for practical implementation of DJs. The Challenge Most language programs focus on communication, but this is not always reflected in prompted writing assignments that center linguistic structure. Dialogue journals provide an alternative that allows students to communicate with their instructor on a topic they choose. This article aims to understand how journals compare to more traditional approaches.